A comparison of approaches to identify possible cases of local anesthetic systemic toxicity in the FDA Adverse Event Reporting System (FAERS) database. Issue 6 (3rd June 2018) - Dagenais, Simon; Scranton, Richard; Joyce, Andrew R.; Vick, Catherine C.
ABSTRACT: Background : Local anesthetic systemic toxicity (LAST) is a rare but potentially serious adverse event . Methods : Data from the US Food and Drug Administration Adverse Event Reporting System were examined for liposomal bupivacaine (LB), bupivacaine, or other injectable local anesthetics. Possible LAST cases were identified based on MedDRA system organ classes (Approach 1), a recent publication (Approach 2), and a novel approach based on LAST literature (Approach 3). Disproportionality analyses compared possible LAST cases for LB and bupivacaine with other injectable local anesthetics. Results : Approaches 1, 2, and 3 identified 75, 42, and 29 possible LAST cases associated with LB, respectively, compared with 9, 595, 3, 422, and 549 for other injectable local anesthetics. The proportional reporting ratios (95% CI) for LB versus other injectable local anesthetics for the 3 approaches were 1.9 (1.6–2.3), 2.9 (2.2–3.9), and 1.6 (1.1–2.2), respectively. Based on sales data, the estimated incidence of possible LAST with LB was 0.1 per 10, 000 uses; literature estimates for LAST with other injectable local anesthetics were 0 to 18 per 10, 000 uses. Conclusions : Our findings suggest the estimated incidence of possible LAST cases with LB is similar to, or less than, the reported incidence with other injectable local anesthetics.